Innovative Behavior on the State Civil Apparatus - Wati, Ratna; Achmad, Mansyur; Toana, Ahmad Averus (Dinasti International Journal of Economics, Finance & Accounting, 2023)
In entering the globalization era with various challenges that exist it will requires us to adjust to that situation. One way to adjust to this dynamic changes is through innovate. This research include in qualitative research by systematic literature research method that intensive and in-depth. In this research, the author tries to identify, collect, investigate and evaluate all the literature used to inform the readers. The researcher collects all the literature in the form of scientific journals/thesis/dissertation related to the innovative behavior of Civil Servants in Indonesia from the Google Scholar database source and produces 38 (thirty-eight) for screening categorization and only 8 (eight) documents related to innovative behavior of Civil Servants. The author conducts a thematic analysis by explaining in problem boundaries section so the important factors regarding an innovative civil servants could be obtained. From these analysis results, it can be concluded that innovative behavior consists of internal factors such as self-efficacy, openness to experience, creativity and psychological capital. Beside that, there are also an external factors such as job demands and job resources, organizational climate and culture, knowledge management and leadership. Thus, the managerial implications for Civil Services needs to transform the mindset by fostering self-efficacy in their environment so as to try new ways or methods in completing work, as well as being open and willingness to accept new ideas from others and sharpening creativity in solving problems.